Effect of Banana Extract on Growth and Development of Protocorm Like Bodies in Dendrobium sp. orchid (The Agriculturists, 2016)
An experiment was carried out in Plant Tissue Culture Laboratory, Department of Crop Botany, Bangladesh Agricultural University, Mymensingh to investigate the effect of banana extract on micropropagation of  Dendrobium sp. var. Sonia orchid through PLBs. The experiment was conducted during July 2012 to October 2013. Half-Murashige and Skoog (1/2MS) medium were used as basal medium and the medium was supplemented with banana extract at 12.5, 25, 50, 100, and 200 ml L-1 with a control, where no banana extract was supplemented. The cultures were done in 100 ml conical flasks and maintain at 25°C with 30µ mol m-2 S-1 lighting provided by florescent tubes for 16 hours per day. Banana extract showed significant effect on growth and development of PLBs. Among the treatments, 100 ml L-1 banana extract enhanced new PLBs regeneration from explanted PLBs and growth and development of PLBs. Present research indicated that nutrient requirement for PLBs multiplication and plantlets growth of  Dendrobium orchid is quantitatively different in vitro. Finally, 100 ml L-1 and 25 ml L-1 of banana extract may be recommended as supplement into 1/2MS medium for PLBs multiplication and plantlet regeneration, respectively in vitro.The Agriculturists 2015; 13(1) 101-108